Systematic Literature Review of Clinical, Economic, and Humanistic Outcomes Following Minimally Invasive Glaucoma Surgery or Selective Laser Trabeculoplasty for the Treatment of Open-Angle Glaucoma with or Without Cataract Extraction - Cantor L; Lindfield D; Ghinelli F; Świder AW; Torelli F; Steeds C; Dickerson JE Jr; Nguyen DQ (Clinical Ophthalmology, 2023)
Louis Cantor,1 Dan Lindfield,2 Federico Ghinelli,3 Anna W Świder,3 Francesca Torelli,3 Carolyn Steeds,3 Jaime E Dickerson Jr,4,5 Dan Q Nguyen6 1Eugene and Marilyn Glick Eye Institute, Indiana School of Medicine, Indianapolis, IN, USA; 2Royal Surrey County Hospital, Guildford, England, UK; 3Valid Insight, Macclesfield, England, UK; 4Sight Sciences, Menlo Park, CA, USA; 5North Texas Eye Research Institute, University of North Texas Health Science Center, Fort Worth, TX, USA; 6Mid-Cheshire Hospitals NHS Foundation Trust, Crewe, UKCorrespondence: Francesca Torelli, Valid Insight, Ropewalks, Newton St, Macclesfield, SK11 6QJ, UK, Tel +44 203 750 9833 Ext 703, Email ftorelli@validinsight.comIntroduction: Selective laser trabeculoplasty (SLT) and minimally invasive glaucoma surgery (MIGS) are increasingly used options for mild-to-moderate open-angle glaucoma (OAG) care. While most MIGS devices are indicated for use in combination with cataract surgery only, with phacoemulsification playing a role in lowering IOP, newer technologies can also be used as standalone glaucoma surgery.Methods: This systematic literature review (SLR) aimed to assess the clinical, economic, and humanistic outcomes of MIGS and SLT for the treatment of OAG and was conducted according to PRISMA guidelines. Studies that assessed MIGS or SLT in at least one treatment arm versus any other glaucoma treatment in adults with mild-to-moderate OAG were included. Clinical, humanistic (health-related quality of life [HRQoL] and patient burden), and economic data were extracted, and the methodological quality of included studies was evaluated.Results: A total of 2720 articles were screened, and 81 publications were included. Fifty-eight reported clinical outcomes. The majority assessed iStent or iStent inject (n=41), followed by OMNI (n=9), gonioscopy-assisted transluminal trabeculotomy (GATT) or the Kahook Dual Blade (KDB) (n=7), Hydrus (n=6), SLT (n=5), Xen Gel Stent (n=2), PreserFlo (n=1), and iTrack (n=1). IOP reduction was observed across prospective studies, varying from − 31% to − 13.7% at month 6 and from − 39% to − 11.4% at year 1 versus baseline. Most adverse events were transient and non-serious. Limited humanistic and economic data were identified.Conclusion: Given their established efficacy and safety, there is a rationale for wider use of MIGS in mild-to-moderate OAG. Of the MIGS devices, iStent and OMNI have the largest clinical evidence base supporting their sustained effectiveness.Keywords: intraocular pressure, IOP, iStent, MIGS, OMNI, SLT